Common Fundamentals of Psoriasis and Depression - Stefanie Hölsken (Society for Publication of Acta Dermato-Venereologica, 2021)
Psoriasis is an inflammatory, immune-mediated disease that is frequently associated with psychological comorbidities such as depression. The stigma patients feel because of the appearance of their skin may contribute to the high psycho-social burden of psoriasis. However, there is emerging evidence that overlapping biological mechanisms are, to a substantial degree, responsible for the close interaction between psoriasis and depression. Increased proinflammatory mediators, such as C-reactive protein or interleukin-6, are present in both psoriasis and depression, indicating that inflammation may represent a pathophysiological link between the diseases. Anti-inflammatory biologic therapies treat the clinical manifestations of psoriasis, but might also play a significant role in reducing associated depressive symptoms in patients with psoriasis. Comparison between single studies focusing on the change in depressive symptoms in psoriasis is limited by inconsistency in the depression screening tools applied.